Depth-wise variations of soil physicochemical properties in the apple growing area of Mustang district, Nepal - Amgain, Rita; Khadka, Dinesh; Joshi, Sushila; Malla, Rajan (Journal of Agriculture and Natural Resources, 2020)
Understanding the soil fertility is an important management tool in assessing the nutrient requirement of the crops. Considering this, a study was done to determine depth-wise soil parameters distribution in the apple growing areas of Gharpajhog Rural Municipality, Mustang during October 2019. The total 68 sampling points were selected randomly in the different sites, and collection was done from three depths viz. 0-20cm, 20-40cm and 40-60cm by using soil sampling auger. The soil separates, pH, organic matter, total N, available P2O5 and K2O were determined following standard methods in National Soil Science Research Centre, Khumaltar. The results of the study revealed that the effect of depth was significant in the sand and silt proportion, while non- significant in clay proportion. The highest (40.17±1.57%) sand content was in 40-60cm depth, meanwhile highest (45.64±1.07%) silt content was in surface (0-20cm) depth. In addition to this, soil pH, OM, total N, available P2O5 and K2O were also affected by the depth. The highest (8.27) pH was determined in the lower (40-60cm) depth. On the other hand, highest OM (4.93±0.2%), total N (0.24±0.01%), available P2O5 (43.47±4.35 mg/kg) and available K2O (95.91±5.8 mg/kg) in surface (0.20 cm) depth. The surface depth possessed strong content of studied soil parameters might be due to in-situ incorporation of leaf litter, residue etc. as well as applied manure in the surface. Finally, we can also conclude that the adopted current nutrient management practice should be continued for apple production in the study area.